2019
DOI: 10.1021/acsnano.9b05493
|View full text |Cite
|
Sign up to set email alerts
|

Surface Charge Switchable Supramolecular Nanocarriers for Nitric Oxide Synergistic Photodynamic Eradication of Biofilms

Abstract: Biofilm has resulted in numerous obstinate clinical infections, posing severe threats to public health. It is urgent to develop original antibacterial strategies for eradicating biofilms. Herein, we develop a surface charge switchable supramolecular nanocarrier exhibiting pHresponsive penetration into an acidic biofilm for nitric oxide (NO) synergistic photodynamic eradication of the methicillin-resistant Staphylococcus aureus (MRSA) biofilm with negligible damage to healthy tissues under laser irradiation. Or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
315
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 372 publications
(317 citation statements)
references
References 48 publications
2
315
0
Order By: Relevance
“…Almost 90% microorganisms can form biofilms, in which bacterial cells are frequently embedded in a self-produced matrix of extracellular polymeric substances (EPS) which basically consist of polysaccharides, proteins, lipids and extracellular DNA [5,6]. The EPS matrix can act as a protective barrier that confers resistance to nonspecific and specific host defenses during infection and prevents the penetration of antibacterial agents [7,8]. The high resistance towards host immune response and traditional antibacterial therapy makes associated infections more intractable and challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 90% microorganisms can form biofilms, in which bacterial cells are frequently embedded in a self-produced matrix of extracellular polymeric substances (EPS) which basically consist of polysaccharides, proteins, lipids and extracellular DNA [5,6]. The EPS matrix can act as a protective barrier that confers resistance to nonspecific and specific host defenses during infection and prevents the penetration of antibacterial agents [7,8]. The high resistance towards host immune response and traditional antibacterial therapy makes associated infections more intractable and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), as an endogenously produced molecule which plays an important role in physiological and pathophysiological processes such as wound healing and immune responses, has attracted much attention [22]. Recently, NO has been recognized as a broad-spectrum bactericidal agent which is capable of killing bacteria, especially for drug-resistant bacteria [8,15]. NO and its byproducts like nitrogen dioxide, dinitrogen trioxide and peroxynitrite can cause nitrosative and oxidative stresses on bacteria, resulting in lipid peroxidation, rupture of bacterial cell membranes, DNA cleavage and protein dysfunction [15,22].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, we developed a kind of synergistic bactericidal nanocarriers (α‐CD‐Ce6‐NO‐DA) that could not only show pH enhanced penetration into biofilm of photosensitizers, but also exhibit improved PDT efficacy with the assistance of nitric oxide (NO) (Figure 5). 114 …”
Section: Therapeutic Methods Of Bacterial Infections With Serious Antmentioning
confidence: 99%
“…(A) Schematic diagram of the preparation process of α‐CD‐Ce6‐NO‐DA nanocarriers. (B) Schematics of the mechanisms of the MRSA biofilm‐associated infection eradication by synergistic effects between ROS (reactive oxygen species) and NO (nitric oxide) produced by α‐CD‐Ce6‐NO‐DA nanocarriers 114 …”
Section: Therapeutic Methods Of Bacterial Infections With Serious Antmentioning
confidence: 99%
“…Besides, it has been reported that bacterial infections and bacterial biofilms provide acidic microenvironments. [ 66 ] Therefore, these factors offer an opportunity to kill bacteria using this pH‐induced charge‐convertible strategy. Qiao et al.…”
Section: Ph‐induced Charge‐convertible Polymer‐mediated Inorganic Nanmentioning
confidence: 99%